2021
DOI: 10.1186/s12544-021-00489-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimating commuting modal split by using the Best-Worst Method

Abstract: Method This paper endeavors to introduce a new approach to modal split estimation. In the frame of the research, a customized model of the recently created Best-Worst Method (BWM) is applied to evaluate mode choice alternatives by transport experts. The integrated BWM model is tested on a real-world case study in Budapest, the capital of Hungary, where a small number of selected experts estimate the modal split of three different groups clustered based on the distance of their commuting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Recently, Duleba et al (2021) suggested a new approach for modal split estimation by ranking mode choice alternatives. Morfoulaki and Papathanasiou (2021) evaluated the most important sustainable mobility measures that should be implemented in urban areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Duleba et al (2021) suggested a new approach for modal split estimation by ranking mode choice alternatives. Morfoulaki and Papathanasiou (2021) evaluated the most important sustainable mobility measures that should be implemented in urban areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, we assumed that the average behavior could be reflected by the model parameters, which were applied for the transportation mode choice estimation. The other studies applied alternative approaches to estimating the modal share under the data limitation, for example, modeling based on the expert survey [35] and statistical model using travel time ratio [36]. They can be candidates for the modal split analysis under the data limitation.…”
Section: Methodsmentioning
confidence: 99%
“…Problem considered Ortega et al [34] Sustainable Park and Ride Facility Location Pamučar et al [35] Renewable Energy Zhou et al [36] Evaluation of Urban Photovoltaic Charging Station Moslem et al [37] Mobility choice after COVID-19 in Italy Kant and Gupta [38] Sustainable Urban Freight Strategies in Jaipur city Ali and Rashid [39] Robot Selection Process Mahmoudi [40] Multiple Experts MCDM problem under uncertainty Ozmen and Aydogan [41] Logistics Center Location Rodrí guez-Gutié rez et al [42] SMEs under sustainability perspective Duleba et al [43] Commuting Modal Spit Guler and Yomralioglu [44] Bicycle Station and Lane Location Selection…”
Section: Referencementioning
confidence: 99%